se alguém souber a resposta dessa questão com cálculo por favor me manda ☝️
Anexos:
![](https://pt-static.z-dn.net/files/d9a/b969287cd794ba8a502a1c4647321d28.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
Alternativa C.
Explicação passo-a-passo:
3(ax + b) = 2(ax - b)
3ax + 3b = 2ax - 2b
3ax - 2ax = - 2b - 3b
ax = - 5b
x = - 5b/a
Perguntas interessantes
Matemática,
8 meses atrás
Química,
8 meses atrás
Matemática,
8 meses atrás
Física,
10 meses atrás
Português,
10 meses atrás
Química,
1 ano atrás